The impact of multilingualism and learning patterns on student achievement in English and other subjects in higher education - Calafato, Raees; Simmonds, Kevin (Cambridge journal of education, 2023)
Students' mindsets, multilingualism, learning styles and self-regulation strategies, which represent parts of their learning patterns, can affect their academic achievement in various ways. This article presents the results of a study that utilised a 185-item online questionnaire to investigate the interplay among the mindsets, learning styles, self-regulation strategies, multilingualism and achievement of 191 undergraduate students in France who were studying English as a foreign language (EFL) as part of their non-language degrees. The findings indicated that students who held growth-oriented mindsets about EFL, used concrete experiences as part of their learning style, and were proficient in multiple languages performed better in EFL. At the same time, there were no statistically significant correlations between their mindsets, learning styles, self-regulation strategies or multilingualism and their achievement in non-language subjects. Interestingly, the students reported employing similar learning styles and self-regulation strategies for both EFL and non-language subjects.